2014
DOI: 10.1371/journal.pone.0088032
|View full text |Cite
|
Sign up to set email alerts
|

TFIIB-Related Factor 2 Over Expression Is a Prognosis Marker for Early-Stage Non-Small Cell Lung Cancer Correlated with Tumor Angiogenesis

Abstract: BackgroundThe aim of this study was to examine BRF2 expression in patients with non-small cell lung cancer (NSCLC) and explore the relationship of BRF2 protein with clinicopathologic factors, tumor angiogenesis and prognosis.MethodsBoth BRF2 protein and intratumoral microvessels were examined by immunohistochemical staining in 107 non-small cell lung cancer patients. Intratumoral m icrovessel density (MVD) was measured by counting CD-34 positive immunostained endothelial cells. Western blot and RT-PCR analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Samples from 107 patients diagnosed with NSCLC and treated with pulmonary lobectomy plus regional lymph node dissection were analyzed for BRF2 expression in lung tumor samples and compared to adjacent normal lung tissue. This study found an overexpression of BRF2 in these tissues and in addition, found a correlation with BRF2 expression and tumor relapse which was associated with unfavorable overall survival [27].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Samples from 107 patients diagnosed with NSCLC and treated with pulmonary lobectomy plus regional lymph node dissection were analyzed for BRF2 expression in lung tumor samples and compared to adjacent normal lung tissue. This study found an overexpression of BRF2 in these tissues and in addition, found a correlation with BRF2 expression and tumor relapse which was associated with unfavorable overall survival [27].…”
Section: Introductionsupporting
confidence: 59%
“…Additionally, the prevalence of a smoking history and squamous cell carcinoma was also significantly associated with BRF2 status [26]. To further investigate the role of BRF2 as an oncogene and as a potential biomarker in NSCLC, Lu et al analyzed the relationship of BRF2 expression with variable clinicopathologic features and patient prognosis in NSCLC [27]. Samples from 107 patients diagnosed with NSCLC and treated with pulmonary lobectomy plus regional lymph node dissection were analyzed for BRF2 expression in lung tumor samples and compared to adjacent normal lung tissue.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The mortality and morbidity of lung cancer is still rising worldwide, especially in developing countries, partly because of the air pollution. 2 Based on the clinical and histologic proof, lung cancer can be divided into small-cell lung cancer and non-small-cell lung cancer (NSCLC). NSCLC accounts for 85% of the primary bronchogenic carcinomas and has the highest mortality rate of malignant tumors in the world.…”
Section: Introductionmentioning
confidence: 99%
“…It was known that Brf1 and Brf2 are differentially expressed in cancers [28] and that Brf2 appears to be oncogenic in lung, where its increased levels indicate poor prognosis [29, 30]. …”
Section: High Resolution Tfiiib Structure Predicts New Functionmentioning
confidence: 99%